Intermediate turbidity elicits the greatest antipredator response and generates repeatable behaviour in mosquitofish. (December 2019) - Ehlman, Sean M.; Halpin, Rebecca; Jones, Cameron; Munson, Amelia; Pollack, Lea; Sih, Andrew
Abstract : Increased turbidity, a common human-induced aquatic disturbance, can potentially have major impacts on predator–prey interactions via effects on key foraging and antipredator behaviours, on the repeatability of these behaviours (i.e. on animal personalities) and on behavioural syndromes (correlations among behaviours). Here, we repeatedly assayed individual western mosquitofish, Gambusia affinis, across a range of turbidity levels (low, intermediate, high) to test the degree to which a suite of behaviours (activity, exploration, sociality, responses to olfactory predator cues) scaled with increasing turbidity. In particular, we tested the a priori hypothesis, based on previous work, that fish show stronger behavioural repeatability and behavioural correlations when perceived predation risk is high. While individuals in all treatments responded to predator cues by reducing activity and exploration, those assayed in intermediate turbidity exhibited the strongest antipredator responses. Consistent with our prediction that repeatability should be greatest in high risk, significant behavioural repeatability was only detected in antipredator behaviours at intermediate turbidity. Significant correlations among behavioural traits were detected in all turbidity treatments but primarily under threat of predation – not when predator cues were absent (with one exception). This study demonstrates that levels of human-induced environmental change may interact with predation risk to shape both mean behavioural responses as well as patterns of behavioural correlations within and among individuals. Highlights: Anthropogenic turbidity affects visually mediated behaviours in mosquitofish. Turbidity interacted with predation risk to affect behavioural repeatability. Antipredator behaviours were greatest in intermediate turbidity. Repeatability most clearly elevated when antipredator behaviours were most intense.